2019
DOI: 10.1016/j.jclepro.2019.06.233
|View full text |Cite
|
Sign up to set email alerts
|

Widening understanding of low embodied impact buildings: Results and recommendations from 80 multi-national quantitative and qualitative case studies

Abstract: Widening understanding of low embodied impact buildings: results and recommendations from 80 multinational quantitative and qualitative case studies. Journal of Cleaner Production, 235 pp. 378-393. For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 70 publications
2
38
0
Order By: Relevance
“…Where available, the literature review was concentrated to LCA studies in a Northern European setting as to account for equivalent design and construction techniques, along with requirements stemming from climatic conditions. While LCA studies of buildings are prevalent, studies that describe and separate material inputs, material transports, and construction processes are more limited, particularly regarding non-residential buildings and refurbishments (see, e.g., reviews in Reference [55][56][57]). As LCA studies are limited for refurbishments, no detailed breakdown for refurbishments has been developed here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Where available, the literature review was concentrated to LCA studies in a Northern European setting as to account for equivalent design and construction techniques, along with requirements stemming from climatic conditions. While LCA studies of buildings are prevalent, studies that describe and separate material inputs, material transports, and construction processes are more limited, particularly regarding non-residential buildings and refurbishments (see, e.g., reviews in Reference [55][56][57]). As LCA studies are limited for refurbishments, no detailed breakdown for refurbishments has been developed here.…”
Section: Methodsmentioning
confidence: 99%
“…Additional upwards adjustments are based on literature detailing refurbishments which report the main embodied emissions resulting from insulation, windows and metals for new ventilation, and heating systems [55,151,152].…”
Section: Estimate and Validation Of Current Emissions From Building Cmentioning
confidence: 99%
“…Strategies for mitigating embodied building emissions currently focus on the reduction of building construction and demolition waste, i.e. extending the existing building life and reuse of existing structures 16 , on the enhancement of the material efficiency, i.e. using less of the same material while providing the same service 17 , or material substitution, i.e.…”
Section: Existing Climate-neutral Strategies In the Built Environmentmentioning
confidence: 99%
“…Due to the significance of this sector in mitigating global climate change, considerable efforts have been undertaken across many countries to reduce energy consumption in residential buildings by legislating various regulations and building codes. These regulations are mainly in place to minimize the environmental impacts associated with energy use from heating, cooling, and lighting [4]. However, recent studies have shown the reduction of building operational energy use can lead to an increase in total building life cycle energy use due to increasing the embodied energy from the building components [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing amount of research has however caused an issue of variations in results presented by LCEA studies, in which apparently similar case studies exhibited different results. To date, a plethora of studies have been conducted exploring reasons for variations in the results of LCEA studies [4,[10][11][12][13]. For instance, Dixit et al [10] identified key parameters which can lead to varying results in embodied energy analysis, namely system boundary definitions, the methods used for measurement of embodied energy, geography, the type of energy (i.e., primary or secondary energy), age and source of data, data completeness, manufacturing technology, feedstock energy considerations, and temporal representativeness.The majority of the conducted studies only looked at parameters with potential influence on calculating embodied energy, whereas variations can also be induced from the measurement of building operational energy.…”
mentioning
confidence: 99%